P1-S1.51 Prevalence of anogenital Warts among STD clinic patients-STD surveillance network, USA, January 2010–September 2010. (10th July 2011) - Llata, E; Pugsley, R; Tabidze, I; Asbel, L; Bernstein, K; Kerani, R; Schwebke, J; Longfellow, L; Mettenbrink, C; Guerry, S; Zenilman, J; Klingler, E; et al.
Abstract : Background: STD clinics routinely provide diagnostic and treatment services for anogenital warts. With the availability and increasing use of a highly effective quadrivalent vaccine against the HPV types associated with 90% of anogenital warts, the impact on patients presenting with anogenital warts to STD clinics may be significant. To be positioned to estimate the population-level impact of HPV vaccine on STD clinics, we conducted a baseline cross sectional analysis of patients with anogenital wart-related visits. Methods: We reviewed STD clinic data collected on patients seen by a clinician from 1 January 2010 to 30 September 2010 in 11 sites (38 clinics) participating in the STD Surveillance Network (SSuN)—Seattle, WA (1 clinic); San Francisco, CA (1); Los Angeles, CA (12); Denver, CO (1); Chicago, IL (5); New Orleans, LA (1); Birmingham, AL (1); Richmond, VA (3); Baltimore, MD (2); Philadelphia, PA (2); New York City, NY (9). SSuN uses a collaboratively developed protocol to collect demographic, risk behaviour, and clinical data on all patients with anogenital warts at participating STD clinics. The unit of analysis was unique patients; patients were considered to have anogenital warts if warts were identified at any visit. Results: Among SSuN sites, 3–13% (median 4%) of STD clinic patients had anogenital wart-related visits, with 5063 patients presenting for 6989 visits. Among patients with anogenital warts, 20% of the patients had multiple anogenital warts-related visits (range 2–26 visits). Overall, the median prevalence rate was 2% (range 1–5%) for women and 6% (range 4–22%) for men. By age and sex, median prevalence rates were highest among women aged 20–24 at 3% (range 1–7%) and among men aged 25–29 at 8% (range 5–25%). Among men who have sex with men (MSM), the median prevalence was 7% (range 4–18%) and among men who have sex with women only (MSW) it was 6% (range 3–23%). Of patients with anogenital warts, 40% were African American, 32% were white, 21% were Hispanic compared to all clinic patients who were 58% African American, 18% white, and 18% Hispanic. 59% received treatment and most treatment (97%) was provider applied. Conclusions: The prevalence of anogenital warts among women is low in STD clinics. It may thus be difficult to monitor the impact of the HPV vaccine in women in these settings. However, the higher prevalence in MSM and MSW suggest that these clinics may provide settings in which to monitor anogenital warts in men.